Evaluation of mastectomy with immediate autologous latissimus dorsi breast reconstruction following neoadjuvant chemotherapy and radiation therapy: A single institution study of 111 cases of invasive breast carcinoma. Issue 7 (July 2016) - Paillocher, N.; Florczak, A.S.; Richard, M.; Classe, J.M.; Oger, A.S.; Raro, P.; Wernert, R.; Lorimier, G.
Abstract: Purpose: The aim of the study was to evaluate morbidity and patient satisfaction following surgically treated skin-sparing mastectomy (SSM) with immediate breast reconstruction (IBR) following mastectomy with neoadjuvant chemotherapy (NACT), and preoperative radiotherapy (RT), for operable invasive breast cancer. Patients and methods: This retrospective single-institution study included 111 patients who underwent a mastectomy with IBR after RT and/or NACT for invasive breast carcinoma at the Institut de Cancérologie de l'Ouest Paul Papin from January 1997 to January 2012. Only patients with breast reconstruction by autologous latissimus dorsi flap with (LDI) or without (ALD) implant were considered. The primary endpoints were the delay in therapeutic sequence, post-operative complication rate, surgical revision rate, time of hospitalization and the anonymous analysis of the patient satisfaction survey. Results: 111 patients underwent mastectomy after RT. The median age was 48 years old and the median body mass index (BMI) was 23.6. SSM were performed in 94.5% of cases. The median interval between the end of chemotherapy (CT) and the beginning of RT was 30 days while the median interval between the end of RT and surgery was 41 days. The rate of primary complications was 66.6% including seroma secretion (reduced to 10.8% when seroma secretion was excluded). The necrosis rate was 5.4%. The average patient satisfaction score for the reconstruction was 17 out of 20. Five-year disease-free and overall survival rates were 93.2% and 98.3% respectively with a median follow-up of 31.6 months. There was only one case of local relapse diagnosed after seven years of follow-up. Conclusion: This study shows that our therapeutic sequence does not appear to increase IBR morbidity and remains within the acceptable safety margins of oncological treatment. It also gives a high quality aesthetic result that helps to maintain patient self-esteem. Abstract : This study shows that skin – sparing mastectomy with immediate breast reconstruction after chemotherapy and preoperative radiotherapy is feasible, has acceptable morbidity, and high patient satisfaction.